Census and contemporary effective population size of two populations of the protected Spanish Moon Moth (Graellsia isabellae). Issue 2 (17th September 2018) - Marí‐Mena, Neus; Naveira, Horacio; Lopez‐Vaamonde, Carlos; Vila, Marta
Abstract: Graellsia isabellae is a protected lepidopteran both in France and Spain; however, there has been considerable debate over its conservation status. Recent literature emphasised the need of monitoring population size in the different mountain ranges where this iconic species occurs. We used mark–capture–recapture and genotypes of nine molecular microsatellite markers to estimate the census ( N ) and contemporary effective population size ( N e ) of two Spanish populations extending over similar size areas (10–15 km 2 ): Puebla (Eastern Spain) and Ordesa (Western Pyrenees). Only adult males were captured and analysed, as sampling was based on the use of the synthesised female sex pheromone. Estimates of N were rather different in the two populations: 3398 males in Puebla (95% CI = 2875–4145) and 1500 in Ordesa (95% CI = 1229–1932), although the area occupied by the populations was larger and more densely forested in Ordesa than in Puebla. Several lines of evidence pointed to a moderate–large contemporary N e at Puebla (173–178 individuals) and a one‐order of magnitude lower N e at Ordesa (27–49). Thus, N e / N ratios were very low (0.026 and 0.01 respectively). We recommend G. isabellae to be classified as of Least Concern under the IUCN criteria; however, the high temporal fragmentation index and the very low values of the N e / N ratios obtained for this species, as compared with those recorded for most others, are usually taken as indicators of actual threat for their conservation. As a cautionary measure, managers should aim at maintaining gene flow by ensuring connectivity of Pinus sylvestris in these areas.